Physicochemical Characterization and Fatty Acid Profiles of Catfish Oil (Clarias gariepinus) - Ningrum, Karina Primatyas; Rohman, Abdul; Martien, Ronny (Journal of Food and Pharmaceutical Sciences, 2023)
Indonesian aquaculture cultivation production of catfish has been growing faster than other fish. It is a potential source of fish oil and contains polyunsaturated fatty acids that have health benefits. The objective of this study was to perform physicochemical characterization and fatty acid profile of catfish oil. This study used fish oil extracted from the head and the flesh of catfish using dry rendering with a mechanic press. The result showed that catfish flesh oil (CFO) and catfish head oil (CHO) were significantly different parameters (p<0.05) in terms of physicochemical characteristics including acid value, peroxide value, iodine value, and saponification value. The best characteristics are catfish flesh oil than catfish head oil for acid value, peroxide value, iodine value, and saponification value following the number is 2.17 mg KOH/g, 5.15 meqO2/kg, 76.13 I2/100 g, 175.86 mg KOH/g. The predominant fatty acids were oleic, palmitic, and linoleic acids. These catfish oils are found suitable for consumption for beneficial health effects.